The performance of the vehicular communication-clustering process - Omar Daoud; Ahlam Damati; Qadri Hamarsheh (Universitas Ahmad Dahlan, 2020)
For the new wireless systems and beyond, the intelligent transportation system is considered as one of the main features that could be covered in the new research topics. Furthermore, both high-speed data transmission and data processing play a crucial role for these generations. Our work covers two main propositions in order to attain an improvement in such intelligent systems performance. A clustering algorithm is proposed and presented for grouping mobile nodes based on their speeds with some modified head assignments processes. This will be combined with a parallel-processing technique that enhances the QoS. Mainly, this work concerns enhancing the V2V data transmission and the processing speed. Thus, a wavelet processing stage has been imposed to optimize the transmitted power phenomenon. In order to check the validity of such proposition, five main efficiency factors have been investigated; namely complementary cumulative distributions, bit rates, energy efficiency, the lifetime of cluster head and the ordinary nodes reattaching-head average times.